Modern Islamic Boarding Schools as Pillars of Contemporary Islamic Education: A Historical Review and Curriculum at Dayah - Juliana, Juliana; AR, Muhammad; Saiful, Saiful (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
As one of the oldest forms of Islamic education in the archipelago, dayah has undergone significant transformations in response to the challenges of the times. This study examines the historical and curricular role of Dayah Modern Darul Ulum YPUI Banda Aceh as a pillar of adaptive and progressive contemporary Islamic education. The research was conducted using a qualitative approach through historical methods and field studies, including interviews, observations, and institutional documentation. The results of the study show that the transformation of the education system in this dayah includes the integration of classical Islamic knowledge (kitab kuning) and the national curriculum, participatory collective leadership, and adaptation to formal education regulations such as Law No. 18 of 2019 and Qanun Aceh No. 9 of 2018. The curriculum is designed holistically with a thematic approach and the instilling of values of adab. The educational process takes place not only in the classroom but also through boarding school care, spiritual activities, and alumni involvement. The important findings of this study confirm that the integrative model applied not only preserves the authenticity of Islamic scholarly traditions, but also strengthens the competitiveness of graduates in facing the demands of the 21st century. The active participation of alumni and legal legitimacy through state policies show that modern dayahs are able to synergize with the national education system without losing their cultural identity.